Development of ground station display and flight management system for low-cost vehicle - Pan, Jing (Cranfield University, 2011)
Nowadays, with the development of electronic and communication technologies, more and more low-cost vehicles such as small, light-weight aircraft are widely applied in all kinds of fields. Ground Station is an essential part of low cost vehicles for the operator to control and monitor the vehicles. In this thesis, Ground Station Display and Flight Management System for Low-Cost Vehicles have been developed.The major objective of this project is to design an intuitive and easy operative Human Machine Interface for displaying and monitoring the flight data and traffic information on ground. Meanwhile, a Graphic User Interface for the Flight Management System has been developed for realizing the waypoints input and flight plan for the vehicles. To fulfill this task, a low-cost hardware and software architecture is presented. Moreover, some COTS tools such as VAPS and MATLAB are applied for the software development because of their Object-Oriented and Rapid Prototype design methods. At the end of project, simulation has been done for the display HMI to test the behaviours of objects and the impacts of display. The trajectory simulation of flight management control panel is also implemented to test the waypoints creation, trajectory generation and smoothing.
Keywords: COTS; GUI; HMI; Object-Oriented Design; Rapid Prototype; VAPS; MATLAB; simulation; waypoint; trajectory generation; trajectory generation